2017
DOI: 10.1167/iovs.16-21130
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Glutamate and γ-Aminobutyric Acid Expressions in Normal and Myopic Eye Development in Guinea Pigs

Abstract: Taken together, our findings suggest that the RGG has a pivotal role in eye development and myopia. The abnormal retina signal induced by the unbalanced ratio between Glu and GABA is related closely to the occurrence of myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…These predictions have been widely confirmed and confirmed in previous experiments. For example, studies by Guoping et al confirmed that cyclic adenosine monophosphate activates retinal apolipoprotein A1 expression and inhibits myopia growth [ 49 ]. Ikuno et al's study showed that glutamic acid can regulate excitatory neurotransmitters in the retina and thus play a pivotal role in eye development and lens-induced myopia (LIM) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These predictions have been widely confirmed and confirmed in previous experiments. For example, studies by Guoping et al confirmed that cyclic adenosine monophosphate activates retinal apolipoprotein A1 expression and inhibits myopia growth [ 49 ]. Ikuno et al's study showed that glutamic acid can regulate excitatory neurotransmitters in the retina and thus play a pivotal role in eye development and lens-induced myopia (LIM) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported down-regulation of GABA-related genes or retinal GABA content during lens and occlusion myopia induction [ 51 , 58 , 105 , 106 ], however, most reports are consistent with the increase in GABA pathway signalling suggested here. Specifically, the present findings are in agreement with previous reports of up-regulation of the NSF protein during lens-induced myopia in mouse [ 63 ], and up-regulation of the GABA A receptor mRNA and protein [ 107 ] and increased retinal GABA content during lens-induced myopia in guinea pigs [ 107 , 108 ]. This pattern of expression responses is also consistent with drug studies showing that GABA receptor antagonists inhibit myopia development [ 105 , 109 , 110 ].…”
Section: Discussionsupporting
confidence: 93%
“…Guoping et al . reported that the ratio of glutamate to GABA was upregulated in myopic guinea pig eyes, suggesting that the ratio of excitatory and inhibitory neurotransmitters may be important for myopic eye growth. Several studies in animals and humans implicate defects in glutamate receptors with myopia .…”
Section: Ocular Diurnal Rhythms and Eye Growthmentioning
confidence: 99%